Gait bradykinesia and hypometria decrease as arm swing frequency and amplitude increase - Zampier, Vinicius C. [UNESP]; Vitório, Rodrigo [UNESP]; Beretta, Victor S. [UNESP]; Jaimes, Diego A.R. [UNESP]; Orcioli-Silva, Diego [UNESP]; Santos, Paulo C.R. [UNESP]; Gobbi, Lilian T.B. [UNESP] (Elsevier, 2018)
People with Parkinson's disease (PD) have decreased arm swing movements during walking, which can be related to PD motor signs and symptoms. In this context, the aim of this study was to determine the effects of an increased arm swing frequency or amplitude on the gait parameters in people with PD and healthy older adults. Seventeen individuals with PD and 19 older people were invited to walk on a 10 m pathway under three experimental conditions: (i) usual walking (no arm swing instructions); (ii) an increased arm swing amplitude; and (iii) an increased arm swing frequency. Both groups had an increased stride speed, vertical center of mass and arm swing accelerations and decreased double support time under the increased arm swing amplitude and frequency conditions. People with PD were able to modulate the gait parameters according to the experimental conditions, but at a smaller magnitude than the older individuals. These results indicate that bradykinesia and hypometria of gait can be positively overcome by increasing the amplitude and frequency of arm swing. Arm movements should be included in gait rehabilitation protocols for PD.
Keywords: Accelerometry; Arm swing; Dynamic balance; Gait spatiotemporal parameters; Parkinson's disease; Walking modulation